Work and Smell : Literature in Comparison - Krause, Frank, (Literatur und Ökonomie ;, 2025)
Literature responds and contributes to the ways in which societies imagine their condition in general and economic life in particular. However, the weighty contribution made by smell motifs to the literary evaluation of working lives has remained underexplored. Work-related smells play an important role in contexts of social inclusion and exclusion, and they can impact strongly on the scope and limits for the fulfillment of needs at work and its surroundings. As emotionally powerful devices, olfactory motifs are also used imaginatively to counter culturally habitualised views on work. The book explores four issues which underpin the nexus of smell and work in literature: the social othering of smelly workers, a sense of social belonging mediated by smell, negative health effects of smelly work environments, and work-related smell in ambivalent contexts of sensual indulgence. The chapters cover European, American and Asian texts and also open up new perspectives for comparative studies.